2017
DOI: 10.1111/jmi.12548
|View full text |Cite
|
Sign up to set email alerts
|

On‐axis versus off‐axis Transmission Kikuchi Diffraction technique: application to the characterisation of severe plastic deformation‐induced ultrafine‐grained microstructures

Abstract: A new configuration for Transmission Kikuchi Diffraction (TKD) in a scanning electron microscope is presented; called 'on-axis TKD'. Compared to the usual off-axis configuration, the scintillator is placed perpendicular to the incident beam under the electron-transparent sample, not in vertical position. In this way, the setup benefits from intense forward scattered electrons enabling short acquisition times. At equivalent diffraction pattern quality, the electron dose needed on the sample is estimated to be 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…The product of the beam current ratio with the applied exposure time ratio resulted in a factor of 20 when measuring with the reference parameters from Table 2 or with lower pattern resolution and exposure time as in Figure 12. This observation confirms the findings by Yuan et al, who reported that for a fixed incident intensity on the specimen in comparison to off-axis TKD the acquisition time is at least 20 times shorter at equivalent pattern quality and indexation rate, and that alternatively 20 times lower electron dose can be used [6].…”
Section: Acquisition Rate 45supporting
confidence: 91%
See 2 more Smart Citations
“…The product of the beam current ratio with the applied exposure time ratio resulted in a factor of 20 when measuring with the reference parameters from Table 2 or with lower pattern resolution and exposure time as in Figure 12. This observation confirms the findings by Yuan et al, who reported that for a fixed incident intensity on the specimen in comparison to off-axis TKD the acquisition time is at least 20 times shorter at equivalent pattern quality and indexation rate, and that alternatively 20 times lower electron dose can be used [6].…”
Section: Acquisition Rate 45supporting
confidence: 91%
“…These limitations triggered the development of a new detector configuration by Fundenberger et al., which consists of a phosphor screen positioned below the sample normal to the incident beam, analogous to TEM [5]. As the acquisition occurs on the axis of the incident beam, TKD in this configuration is termed "on-axis" TKD, compared to conventional "off-axis" TKD [6]. Yuan et al showed that the new configuration leads to high intensity and low gnomonic distortion of acquired Kikuchi patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the conventional EBSD and 'off-axis' TKD configurations, the new 'on-axis' detector geometry, where the optic axis of the SEM intersects the centre of the phosphorous screen, allows acquisitions of Kikuchi patterns directly below the sample where the signal yield is strongest and gnomonic distortions are minimised. This improves the acquisition speed, lateral spatial resolution and indexing rates without sacrificing angular resolution [6][7][8]. Automated crystal orientation mapping in the transmission electron microscope (ASTAR) is capable of achieving a lateral resolution of 1 nm, similar to 'on-axis' TKD, but overlapping of fine grains in the sample thickness will result in the formation of composite diffraction patterns which can lead to deconvolution problems during the template matching process.…”
Section: Introductionmentioning
confidence: 99%
“…TKD (both on-axis and conventional) allows producing orientation maps with a spatial resolution of a few nanometres, which cannot be achieved by EBSD [17,18]. Besides, on-axis TKD is particularly fast; up to a few hundreds of patterns can be automatically recorded and indexed per second [19]. Both TEM and on-axis TKD have been applied in the present study with the objective of characterizing disorientations inside and between growth blocks of a graphite spheroid.…”
Section: Introductionmentioning
confidence: 99%